Challenges and Recommendations of Filariasis Elimination in Asia: A Systematic Review - Abraham Chiu En Loong; Azman Atil; Adora J Muyou; Ahmad Nabeil Alias; Alif Ramli; Ramalingam Thulasiraman; Syed Sharizman Syed Abdul Rahim; Richard Avoi; Fredie Robinson; Mohammad Saffree Jeffree; Mohd Rohaizat Hassan (Universiti Putra Malaysia, 2023)
Introduction: Filaria, a parasitic disease caused by filarial worms, has posed a significant health burden in many countries in Asia. In response, various elimination programs have been implemented in the region to combat the transmission of this disease. While some countries in Asia have successfully implemented these strategies, others continue to face challenges in their elimination efforts. This study utilised a systematic review approach to identify the challenges encountered by Asian countries that have not yet achieved the status of elimination and to provide recommendation. Methods: A comprehensive search of databases, including PubMed, Scopus, and SpringerLink, was conducted based on PRISMA to gather relevant records from 2011 to 2021. The inclusion criteria were limited to Asian countries who that have not achieved elimination. JBI tools for cross-sectional and qualitative studies were used for quality assessment. Results: A total of 14 papers out of 372 papers were included in the review. The challenges identified in the filariasis elimination program in Asia can be categorised into five main themes: poor implementation strategy, poor political will, instability or crises, lack of research and surveillance, and lack of awareness, knowledge, perception among the community and geographical and demographic factors. Conclusion: Overall, this study highlights the importance of understanding and addressing the challenges faced by Asian countries and provide recommendations in their filariasis elimination programs. By acknowledging and actively working to overcome these challenges, health authorities can enhance their efforts to eliminate filariasis and improve the overall health outcomes of affected populations.